Chitosan as Potential De-coloring Agent for Synthetic and Textile Industrial Wastewater - Abdelfattah, Ibrahim; El-Shamy, A. M. (Journal of Environmental Accounting and Management, 2026)
In today's ages, the chitosan biopolymer has ample applications in drinking and wastewater treatment, which is the reason for its large occurrence and fair cost. The potential adsorbent properties are back to its structure since, in addition to its porosity effect, it contains --NH${}_{2}$ and -OH${}^{-}$ groups. In this analysis, the powdered chitosan biopolymer is used as an adsorbent for the abstraction of Remazol Brilliant Blue R (RBB-R). Many variables are studied to enhance the progression of adsorption such as adsorbent dose, pH, interaction time, initial concentration of adsorbents. In addition, the kinetic model's several adsorption isotherms are added to highlight the mechanism and the process of adsorption. Additionally, the degradation efficiency of the actual wastewater treated and untreated was achieved. Finally, to protect the municipal networks, the corrosion of steel pipeline was subjected to evaluation for untreated and treated wastewater to enhance their inhibition of the corrosion process.